Biological analysis of Sonchus oleraceus (Linn) extract and its effect on mitigating sodium benzoate-induced cytotoxicity and genotoxicity - Althubyani, Maryam Abdulmalik; Alrefaei, Abdulmajeed F.; Qari, Sameer Hasan; Alharbi, Rayan S.; Alqathama, Aljawharah (Frontiers in Toxicology, 2025)
BackgroundFolk medicine has long employed plants to treat diseases. Consumers believe herbal treatments are safe since they are natural. Studies suggest that some plant compounds can cause chromosomal damage at high concentrations, while some can mitigate the genotoxicity caused by toxic substances. Sonchus oleraceus L. is a popular medicinal herb in Saudi Arabia as well as in the rest of the world. It has antioxidant, anticancer, and other biological properties. Sodium benzoate (SB) is a versatile food preservative used in packaged food and drink industries; it has been found to cause genotoxicity and DNA damage. Therefore, it is necessary to investigate the biological activity of Sonchus oleraceus extract and its ability to mitigate Sodium Benzoate-induced cytotoxicity and genotoxicity.AimThe current study evaluates biological properties of S. oleraceus leaf extract and reveals its potential mitigating role against sodium benzoate by using the Allium cepa in vivo bioassay and molecular analysis.MethodologyS. oleraceus aqueous extract and sodium benzoate was prepared. Then, the effective concentration (EC50) was determined, and concentrations with control were selected for each group. Roots of A. cepa were treated for 24, 48, and 72 h with concentrations (21.5, 43, and 64.5 mg/mL) of extracts with or without combined treatment with 4 mg/mL of SB for 24 h. The cytotoxicity was investigated by using mitotic index (MI) and the genotoxicity by micronuclei (MN), chromosomal abnormalities (CA) and then using the ISSR-PCR markers for molecular analysis.ResultsCompared to the controls, S. oleraceus and SB application as a single treatment decreased root length and MI index, and CA were increased, especially in higher concentrations. DNA damage was reported by ISSR-PCR markers. However, SB toxicity was mitigated by the co-treatment of S. oleraceus extract, which showed partial improvement in all variables depending on the application concentration, possibly due to its antioxidant properties. The cytogenetic assay showed the best antimutagenic efficacy at 21.5 mg/mL with a moderate inhibition rate greater than 25%.ConclusionThe results indicate that the aqueous extract of S. oleraceus leaves, as a single treatment, induces a genotoxic effect on A. cepa cells, especially at high concentrations, and that S. oleraceus leaf extract, as a co-treatment, acts as a mutagen at high concentrations and a moderate antimutagenic at low concentrations. The findings also indicate that the cytotoxic capacity of SB in A. cepa highlights potential concerns that warrant further investigation.